If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = -5 + b Solving 0 = -5 + b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. 0 + -1b = -5 + b + -1b Remove the zero: -1b = -5 + b + -1b Combine like terms: b + -1b = 0 -1b = -5 + 0 -1b = -5 Divide each side by '-1'. b = 5 Simplifying b = 5
| 2x-4=2x+-2+3 | | y=375-50(15-1) | | -56+4x=10x+16 | | 4-3f=7 | | -12-92=183-x | | -3(x-9)= | | (b+1)*(b-1)= | | 7=48+x | | 4(5y-5)-(3y+8)= | | -9x+15=-4x-70 | | 4x^2+12x+c=y | | 5h-(h+8)=2n | | 6(5a+4)+5a=-11 | | -2(x+2)-3=5 | | -x-(13+4x)=-3(5-9x)+3k | | 2x^2+5x^2-7x-3= | | 2=4r | | 7x-(6x+5)=6x-40 | | 2x^3-6x^2-141x+6=0 | | 2(h+9)-6= | | 6-8(n-4)=-8n+37 | | 0.5x+8=3x+5 | | 10x-75=5x+30 | | w+14=18 | | 6x+10-8x=15-13x+11x-5 | | -10(-3x+3)=30+10x | | (3+x)4+(5x)=66 | | 20-0.5y=12.5 | | 20x-7-5=-52 | | -6(2+2x)=-24 | | .50x+8=3x+5 | | 0=(-4x^2-6x)-1 |